Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1021/acs.biomac.2c01348
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Bottlebrushes for Immunostimulatory CpG ODN Delivery: Relationship among Cation Density, Complex Formation Ability, and Cytotoxicity

Abstract: Artificially designed short single-stranded DNA sequences containing unmethylated CG (CpG ODNs) are agonists for toll-like receptor 9 (TLR9); thus, they have great potential as vaccine adjuvants for cancer immunotherapy and preventing infectious diseases. To deliver effectively CpG ODNs into cells bearing TLR9, nanoparticle polyion complexes of cationic polymers that are able to ingest multiple CpG ODN molecules have been developed; however, their structures and synthesized polycations are hard to control and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Since the surface charge density, σ c , of cNGs is the key parameter for electrostatically driven binding events, 16,54 we quantified this characteristic from the dimensions and ζ-potential values of different cNGs 55 (see details in ESI †) and examined its effect on the binding constant K a of cfDNA to cNGs with varying σ c values. In the 150 mM PBS buffer, the K a value increased from 1.99 × 10 5 to 4.13 × 10 5 M −1 when σ c increased from 2.9 to 15.8 mC m −2 , respectively (Fig.…”
Section: Binding Of Cfdna To Nanogelsmentioning
confidence: 99%
“…Since the surface charge density, σ c , of cNGs is the key parameter for electrostatically driven binding events, 16,54 we quantified this characteristic from the dimensions and ζ-potential values of different cNGs 55 (see details in ESI †) and examined its effect on the binding constant K a of cfDNA to cNGs with varying σ c values. In the 150 mM PBS buffer, the K a value increased from 1.99 × 10 5 to 4.13 × 10 5 M −1 when σ c increased from 2.9 to 15.8 mC m −2 , respectively (Fig.…”
Section: Binding Of Cfdna To Nanogelsmentioning
confidence: 99%
“…However, it has been reported that ICD cannot generate a sufficient antitumor immune response because of the ITM. 14,15 Cytosine-phosphate-guanosine oligonucleotides (CpG ODNs), 16 as toll-like receptor 9 (TLR9) agonists of DCs, can trigger strong immunostimulatory activity via MyD88-dependent NF-κB and MAPK signaling and subsequently promote the release of proinflammatory cytokines such as interleukin 6 (IL-6), IL-12, and tumor necrosis factor-α (TNF-α), ultimately inducing a Th1-like innate immune response and adaptive immunity. 17,18 The antigens generated by ICD can be efficiently delivered to APCs with the aid of the immunoadjuvant CpG.…”
Section: Introductionmentioning
confidence: 99%
“…Spacer segments have been introduced between initiating groups to decrease the reactivity of zwitterionic monomers. , Additionally, bottlebrush zwitterionic polymers with a multiblock structure have been synthesized to explore the effect of intermolecular interactions on their formation. ,, The spatial shape of bottlebrush macromolecules in solution can be explained by Pedersen’s model . By modifying the types and proportions of the copolymerization monomers, zwitterionic bottlebrush polymers with different performances can be obtained. ,,, …”
Section: Introductionmentioning
confidence: 99%